2013
DOI: 10.1002/nme.4583
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of techniques for overcoming non‐uniqueness of boundary integral equations for the collocation partition of unity method in two‐dimensional acoustic scattering

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…The CHIEF and Burton-Miller approaches were compared for POU-BEM in [40]. Here the authors concluded that CHIEF outperformed Burton-Miller, though implementation details such as regularising coordinate transforms appear to have had a significant effect.…”
Section: Non-uniquenessmentioning
confidence: 98%
See 3 more Smart Citations
“…The CHIEF and Burton-Miller approaches were compared for POU-BEM in [40]. Here the authors concluded that CHIEF outperformed Burton-Miller, though implementation details such as regularising coordinate transforms appear to have had a significant effect.…”
Section: Non-uniquenessmentioning
confidence: 98%
“…Here the authors concluded that CHIEF outperformed Burton-Miller, though implementation details such as regularising coordinate transforms appear to have had a significant effect. It is worth pointing out here that regularisation of the hypersingular operator, which occurs in the Burton-Miller formulation, is rather challenging for collocation schemes, as was used in [40]. In contrast, Galerkin schemes allow the hypersingular operator to be rewritten in a form that only contains a weak singularity [41,42].…”
Section: Non-uniquenessmentioning
confidence: 99%
See 2 more Smart Citations
“…Diwan et al [34] have recently suggested that CHIEF is a suitable solution to the non-uniqueness problem and is simpler to implement than dealing with the hyper-singular integrals of the Burton-Miller formulation [4]. In addition to the complex integrals of the Burton-Miller formulation, there is another problem that must be addressed: some NURBS meshes have locations at which control points are coincident (e.g.…”
Section: Integration and Solutionmentioning
confidence: 99%